2021
DOI: 10.3390/agronomy12010056
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Soybean Genotypes Based on Root Morphology and Shoot Traits Using the Semi-Hydroponic Phenotyping Platform and Rhizobox Technique

Abstract: Root-system architecture is vital for improving soybean (Glycine max L.) growth and nutrient uptake. We characterised root-system architecture and shoot traits of 30 soybean genotypes in a semi-hydroponic system 35 days after sowing (DAS) and validated eight genotypes with contrasting root-system architecture in 1.5 m-deep rhizoboxes at the flowering stage. Among them, two genotypes were selected for evaluation through to maturity. Abundant variation (coefficient of variation values ≥ 0.25) was observed in 11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…Hydroponics is a high-throughput phenotype screening and identification method which involves culturing plants in a solid support device containing a nutrient solution with essential nutrients for plant growth. Hydroponic phenotyping system has been used to characterize root morphological traits at the early growth stage of various crop species, including soybean ( Chen, 2021 ; Salim et al, 2021 ), barley ( Wang et al, 2021 ), wheat ( Jeudy et al, 2016 ; Rumesh et al, 2019 ; Chen et al, 2020 ), and maize ( Qiao et al, 2019 ). Jeudy et al (2016) developed a new tool for high throughput imaging of root features based on a form of hydroponic called RhizoTubes.…”
Section: Survey Methodologymentioning
confidence: 99%
“…Hydroponics is a high-throughput phenotype screening and identification method which involves culturing plants in a solid support device containing a nutrient solution with essential nutrients for plant growth. Hydroponic phenotyping system has been used to characterize root morphological traits at the early growth stage of various crop species, including soybean ( Chen, 2021 ; Salim et al, 2021 ), barley ( Wang et al, 2021 ), wheat ( Jeudy et al, 2016 ; Rumesh et al, 2019 ; Chen et al, 2020 ), and maize ( Qiao et al, 2019 ). Jeudy et al (2016) developed a new tool for high throughput imaging of root features based on a form of hydroponic called RhizoTubes.…”
Section: Survey Methodologymentioning
confidence: 99%
“…The superiority of the Lee variety may be due to its high efficiency in converting photosynthetic products from the vegetative part of the plant in favor of root growth, increasing division, and elongation of its cells, and then increasing root length. In the same direction as [11,21] that the varieties differ among themselves in root length. It appears from the results of the triple interaction that the Lee cultivar, with the effect of foliar feeding with zinc concentration 100 mg L -1 and arginine 80 mg L -1 concentration, gave the highest average root length of 37.55 while Shaima, in the comparison treatment of zinc and arginine, gave the lowest root length rate of 37.55 cm.…”
Section: Root Length (Cm)mentioning
confidence: 74%
“…In our recent study, root trait variability of 184 bread wheat genotypes originating from 37 countries was characterized in the same semi-hydroponic phenotyping system (Chen et al, 2020), followed by validation of genotypes with contrasting root systems in soil-filled rhizoboxes (Figueroa-Bustos et al, 2018). The consistent ranking of genotypes for some important root traits in the semi-hydroponic system and soil conditions indicates the reliability of the phenotyping study for root studies, as confirmed in other crop species, such as narrow-leafed lupin (Chen et al, 2011a;Chen et al, 2014), barley (Wang et al, 2021), and soybean (Liu et al, 2021;Salim et al, 2022). The wheat lines used in this study will be examined further under the field conditions.…”
Section: Phenotypic Analysis Of Root Traitsmentioning
confidence: 84%